Taguchi Optimization of Screw Flight Bending Operation - Aliemeke, Blessing Ngozi Goodluck; Okwudibe, Henry Adimabuah; Ososomi, Asunumeh Sunday; Dirisu, Braimah (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The optimizations of screw flight bending operating parameters have been successfully carried out. The optimization of the screw flight bending operation, aims at determining optimal values for key parameters using Taguchi Design and Genetic Algorithm (GA) optimization tools. The parameters investigated include bending radius, diameter of screw, flight thickness, and bending force. Through the systematic application of Taguchi methodology and GA optimization, optimal values of 79.99 mm for bending radius, 69.997 mm for diameter of screw, 5.005 mm for flight thickness, and 232.62 N for bending force were identified. The effectiveness of the optimized parameters was assessed through analysis of variance (ANOVA), revealing an R-squared value of 84.78 % and an adjusted R-squared value of 75.64 %. These results indicate that the developed model explains a significant portion of the variability in the response variable, providing confidence in the reliability and significance of the optimized solutions. Overall, the integration of Taguchi methodology with GA optimization has proven to be a powerful approach for systematically exploring parameter space and identifying optimal solutions in screw flight bending operations. The optimized parameter values offer the potential for enhanced performance, accuracy, and efficiency in the bending process, contributing to improved product quality and manufacturing productivity.